Determinants of Firm's open innovation performance and the role of R & D department: An empirical evidence from Malaysian SME's - Waseem Ul Hameed; Muhammad Farhan Basheer; Jawad Iqbal; Ayesha Anwar; Hafiz Khalil Ahmad (Journal of Global Entrepreneurship Research, 2018)
The prime objective of the current study is to investigate the major determinants of firm's open innovation performance in Malaysian small and median-sized enterprises (SMEs). Recently, Malaysian SMEs have suffered from low open innovation performance. These SMEs are still struggling to get success in open innovation adoption. Decline in open innovation practices hampered the overall SMEs performance. To address this issue the current study adopted quantitative research approach and cross-sectional research design. A 5-point Likert scale was used to collect the data through mail survey. Two hundred (200) questionnaires were distributed among the managerial staff of SMEs in Malaysia by using area cluster sampling. Smart PLS3 (SEM) was utilized as a statistical tool. It was found that external knowledge, internal innovation and R & D department were the major determinants of firm's open innovation performance. Thus, the current study contributed in the body of knowledge by revealing the real determinants of open innovation performance and R & D department as a mediator. Therefore, the current study is beneficial for SMEs to boost up the overall performance by accelerating open innovation system.
Keywords: 650; Open innovation; SMEs; External knowledge; Internal innovation; R & D department; Performance